Sustainable Urban Governance and the Digital Divide: Patterns of E-Participation in Istanbul - Kozaman Aygun, Senem; Inal Cekic, Tuba (MDPI, 2025)
Digital transformation in public service delivery holds the potential to foster sustainable urban governance by promoting transparency, inclusivity, and citizen engagement. However, unequal access to digital tools and competencies poses challenges to the equitable use of these services. This study examines how different dimensions of the digital divide-socio-demographic characteristics, digital literacy, physical access to technology, and the perceived necessity of the internet-influence citizen engagement with digital public services in Istanbul. Drawing on secondary data from the Istanbul Metropolitan Municipality, a three-step methodology is employed combining logistic regression, thematic analysis, and spatial comparison. The results indicate that factors such as education, gender, age, and perceived necessity significantly affect digital engagement. Notably, digital literacy does not consistently predict e-government service use, suggesting that necessity may override competence. The study also finds that engagement remains limited to passive information-seeking rather than participatory functions. These findings highlight the importance of addressing digital inequalities to promote more inclusive service access. Ultimately, the study contributes to the understanding of how digital inclusion can advance sustainable urban governance and emphasizes the need for policies that ensure digital platforms benefit all segments of the population.
Keywords: digital divide; sustainable urban governance; citizen engagement; digital public services; e-participation; Istanbul; ADULTS USE; TECHNOLOGY; Science & Technology - Other Topics; Environmental Sciences & Ecology